Cardiac surgery in South Africa: Have we failed our legacy? - Reddy, D; Kleinloog, R; Kinsley, R (SA Heart Journal, 2026)
Cardiac surgery in South Africa (SA) was thrust onto the world stage in 1967 following Christiaan Barnard’s world-first orthotopic heart transplant in Cape Town. This pioneering achievement defined the country as an unlikely leader in daring surgical innovation, clinical excellence and laboratory research.(1) The decades following the first heart transplant launched the speciality on a pathway of surgical excellence, evident by world-class surgeon-leaders and internationally renowned training units. That stellar trajectory has unfortunately reversed, and the current SA cardiac surgery landscape is characterised by the lack of experienced academic leadership, virtually non-existent training and surgical programmes, and the lack of outcomes reporting and benchmarking in both private and public sectors.